Caracterização citoarquitetônica, neuroquímica e de aferência óptica do complexo parabraquial do sagui (Callithrix jacchus) - Engelberth, Rovena Clara Galvão Januário (2010)
The parabrachial complex (PB) is an area of the brainstem responsible for the processing and transmission of essential physiologic information for the survival of the organisms. This region is subdivided in approximately nine subregions, considering morphology, cytoarchitectural and functional characteristic. Its neurons have an extensive network of connections with other regions of the nervous system. The objective in this work was to map the retinal projection to the PB and make a citoarchitectonic and neurochemical characterization of this region in the common marmoset (Callithrix jacchus), a primate of the New World. The retinal projections were mapped by anterograde transport of the choleric toxin subunit b (CTb). The citoarchitecture was described through the Nissl method, and the neurochemical characterization was made through immunohistochemical technique to the some neurotransmitters and neuroactives substances present in this neural center. In marmoset PB, in the coronal sections labeled by Nissl method, we found a similar pattern to that evidenced in other animal species. The immunoreactivity against CTb was verified in the PBMv in fibers/terminal, characterizing such as retinal innervations in this area. The immunohistochemical technique reveled that the PB contain cells, fibers and/or terminals immunoreactives to the neuronal nuclear protein, Choline acetyl transferase, nitric oxide synthase, serotonin, enkephalin, substance P, Calcium-binding proteins (calbindin, calretinin e parvalbumin), and glial fibrillary acidic protein. The histochemical technique reveled cells and fibers NADPH-diaphorase reactive. Each one of those substances presented a characteristic pattern of demarcation in PB, and some serve as specific markers of subregions